Developing RESTful Services with JAX-RS 2.0, WebSockets, and JSON. - Kalali, Masoud (Packt Publishing, 2013)
Written as an easy and practical guide, this book is a crash course on using JAX-RS 2.0, JSON, and WebSockets to develop RESTful services. Getting Started with Developing RESTful Web Services using JAX-RS 2.0, JSON, and WebSockets is a perfect reading source for application developers who are familiar with Java EE and are keen to understand the new HTML5-related functionality introduced in Java EE 7 to improve productivity. To take full advantage of this book, you need to be familiar with Java EE and have some basic understanding of using the GlassFish application server.